Nanomedicine-based disulfiram and metal ion co-delivery strategies for cancer treatment - Xinyue Shen; Huixiang Sheng; Ying Zhang; Xuan Dong; Longfa Kou; Qing Yao; Xinyu Zhao (Elsevier, 2024)
Disulfiram (DSF) is a second-line drug for the clinical treatment of alcoholism and has long been proven to be safe for use in clinical practice. In recent years, researchers have discovered the cancer-killing activity of DSF, which is highly dependent on the presence of metal ions, particularly copper ions. Additionally, free DSF is highly unstable and easily degraded within few minutes in blood circulation. Therefore, an ideal DSF formulation should facilitate the co-delivery of metal ions and safeguard the DSF throughout its biological journey before reaching the targeted site. Extensive research have proved that nanotechnology based formulations can effectively realize this goal by strategic encapsulation therapeutic agents within nanoparticle. To be more specific, this is accomplished through precise delivery, coordinated release of metal ions at the tumor site, thereby amplifying its cytotoxic potential. Beyond traditional co-loading techniques, innovative approaches such as DSF-metal complex and metal nanomaterials, have also demonstrated promising results at the animal model stage. This review aims to elucidate the anticancer mechanism associated with DSF and its reliance on metal ions, as well as to provide a comprehensive overview of recent advances in the arena of nanomedicine based co-delivery strategies for DSF and metal ion in the context of cancer therapy.